2018
DOI: 10.3892/ol.2018.8474
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinamide N‑methyltransferase enhances the progression of prostate cancer by stabilizing sirtuin 1

Abstract: A previous study demonstrated that nicotinamide N-methyltransferase (NNMT) is upregulated in the tissues of patients with prostate cancer (PCa); however, the specific underlying mechanism of this remains unclear. To begin with, the expression of NNMT was investigated in the peripheral blood of patients with PCa and of healthy control subjects. The results indicated that the expression level of NNMT was elevated in the peripheral blood and tissues of patients with PCa. Furthermore, the overexpression of NNMT en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…Hong et al reported that increasing NNMT expression or MNA levels stabilizes SIRT1 protein to regulate hepatic nutrient metabolism [29]. You et al reported NNMT enhances the progression of prostate cancer by stabilizing SIRT1 [30]. These results indicated that NNMT may be a potential therapeutic target not only in cancer but also in other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Hong et al reported that increasing NNMT expression or MNA levels stabilizes SIRT1 protein to regulate hepatic nutrient metabolism [29]. You et al reported NNMT enhances the progression of prostate cancer by stabilizing SIRT1 [30]. These results indicated that NNMT may be a potential therapeutic target not only in cancer but also in other diseases.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38][39] NNMT overexpression has been reported in breast cancer, glioblastoma, and papillary thyroid cancer, among others. 20,40,41 Ulanovskaya et al 42 previously revealed that NNMT overexpression leads to an increase in 1MNA in various aggressive cancer cell lines; the authors proposed that the accumulation of 1MNA caused by NNMT overexpression would sequester methyl groups in cancer cells, leading to diminished methylation with changes in the epigenetic profiles.…”
Section: Discussionmentioning
confidence: 99%
“…, TGF‐beta can indeed upregulate the expression of NNMT in hepatoma cells, and the mechanism will continue to be further studied. NNMT methylates NAM and is expressed at high levels in several cancers (Liang et al , ; Pozzi et al , ; Song et al , ; You et al , ) like renal clear cell carcinoma, bladder cancer, and the gastric and colorectal cancers. NNMT KD has similarly been associated with the inhibition of proliferation and/or metastasis of oral squamous carcinoma, renal clear cell carcinoma cells, Panc‐1 pancreatic cancer cells, etc.…”
Section: Discussionmentioning
confidence: 99%